Singular Solutions to Monge-Ampère Equation (Analysis in Theory and Applications, 2022)
We construct merely Lipschitz and $C^{1,α}$ with rational $α ∈ (0, 1 − 2/n]$ viscosity solutions to the Monge-Ampère equation with constant right hand side.